America's lowest cost colleges - Roes, Nicholas A. (Barryville, NY : NAR Publications, 1991)
On cover: A comprehensive directory of more 1,000 fully accredited colleges and universities with low or no tuition.
Includes index.
Young Adult
Keywords: College costs -- United States -- Directories; Universities and colleges -- United States -- Directories; Universities and colleges -- United States -- Finance -- Directories; College costs -- United States -- Directories; Colleges and universities -- Directories